Ecological Perplexity and Environmental Consideration in Pankaj Sekhsaria’s The Last Wavean Island Novel - Suganth, R.S.; R. , Jinu (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the study is to discuss the environmental issues in the Andaman Islands after the settlement of the people from the mainland and other countries. It further focuses upon tribal literature and tribes that live in the Andaman Islands. It is followed by illegal activities and other schemes followed by the settlers. The schemes create a great threat to the environment and distress the ecology. It discusses some of the illegal activities that ruin human existence in the world. It discusses some incidents of human ascendancy towards nature and how the ecological disputes and controversies are raised. The impact of the dispute leads to destruction in the hands of nature, which decimates the human race. The final note discusses how the problems can be rectified and how to live with nature.